RAISE OF HIGH FROST-RESISTANT AGROPYRON–TRITICUM HYBRIDS - E. P. Razmakhnin; T. M. Razmakhnina; V. E. Kozlov; E. I. Gordeeva; N. P. Goncharov; G. Y. Galitsyn; S. G. Veprev; V. M. Chekurov (Вавиловский журнал генетики и селекции)
One way of obtaining high-frost-resistant varieties of winter wheat is a wide hybridization with wild relatives, in particular, certain species of wheatgrass. The most promising frost resistance donor is Agropyron glaucum (Desf. ex DC) Roem. & Schult. (=Syn. Thinopyrum intermedium (Host) Barkworth & D.R. Dewey). A large collection of Agropyron glaucum genotypes was derived from the original material collected in Eastern Kazakhstan, at an elevated site with little snow, which suggested that they had high frost resistance. A biotechnological approach to obtaining pure androgenous wheatgrass lines via anther culture and an efficient method for rapid analysis of frost resistance in winter wheat, wheatgrass and other crops were developed. The said approach gave rise to androgenous lines with various wheat cultivars, and subsequent backcrossing yielded a diversity of wheat-wheatgrass hybrids. This material is currently being used for creation of frost-resistant varieties of winter wheat and for increasing wheat biodiversity. The described technology shortens the time for production of frost resistant wheat-wheatgrass hybrids to 2–3 years. In addition, experiments on frost resistance transfer from wheatgrass to wheat by means of the leaf nurse method were conducted. When ripe, a few frost-resistant lines of winter wheat obtained displayed elevated productivity and altered morphology of ears, which had long awns, inherited in the progeny. This material is now being studied and propagated.